Motives to take part in therapeutic physical activities of students with disabilities and health problems - Prusińska, Violetta (Akademia Wychowania Fizycznego w Poznaniu)
As an important part of healthy living, disease prevention and methods of coping with stress physical activity should be a priority subject for students with disabilities and health problems. This research shows that students taking part in therapeutic physical activities (rehabilitation, therapeutic gymnastics and yoga) are mainly focused on health and disease prevention. However, additional important motive, especially for healthier students, is the course completion, which is obligatory. The awareness of the students’ needs and motives towards participating in therapeutic classes may allow to adjust the offer of Departments of Physical Education and Sport at Universities to their actual needs and capabilities
Keywords: disabled student; medical physical activities; motivation; physical education